Bridging Linguistic Gaps: A Quantitative Study on the Role of Arabic in Libyan University EFL Classrooms (مجلة العلوم الشاملة, 2025)
The integration of the first language (L1) in English as a Foreign Language (EFL) instruction remains a subject of debate, particularly in contexts where English exposure outside the classroom is limited. This study examines how Libyan university EFL instructors incorporate Arabic (L1) into their teaching, focusing on its frequency, instructional contexts, and influencing factors. Using a quantitative, cross-sectional survey, data were collected from 45 university-level EFL instructors across multiple institutions. The findings reveal that 70% of instructors use Arabic, primarily for vocabulary explanations, classroom instructions, and comprehension support, while 30% follow an English-only approach. However, opinions on incorporating L1 vary, with concerns about potential over-reliance, particularly in grammar instruction and classroom discipline.The study also highlights teaching experience and student proficiency as key determinants of L1 use. More experienced instructors adopt a flexible, strategic approach, whereas less-experienced educators tend to follow monolingual methodologies, reflecting the influence of teacher training programmes. Similarly, L1 use is more common in advanced-level courses, where students engage with complex academic content, while lower-year instructors prioritise English immersion to develop foundational language skills. Additionally, attitudes towards native-like proficiency are shifting, with most instructors emphasising communicative competence over rigid adherence to native-speaker norms.These findings have significant implications for teacher training and institutional policies. The study advocates for evidence-based bilingual pedagogy, recommending that universities move beyond rigid English-only policies and adopt context-sensitive L1 guidelines that align with students’ needs and proficiency levels. Teacher training programmes should also equip instructors with bilingual strategies that balance Arabic support with progressive L2 immersion.Future research should explore student perspectives on L1 integration, assess the long-term impact of bilingual strategies, and investigate the role of digital tools in bilingual instruction. By adopting a balanced, research-informed approach, Libyan universities can enhance English proficiency while utilising Arabic as a valuable learning resource, ensuring that students develop both linguistic competence and academic success.